"Cholera Forcing" and the Urban Water Infrastructure: Lessons from Historical Berlin - Kalle Kappner (European Historical Economics Society (EHES), 2019)
Did cholera function as a potent catalyst for the reform of urban water infrastructure in 19th century Europe's disease-ridden cities, serving as "our old ally" in the struggle for urban sanitation (Robert Koch)? Based on a detailed case study of Berlin's hydrological reconfiguration, this paper challenges popular narratives that paint the emergence of safe tap water supplies and sanitary sewers as an efficient, scientifically motivated reaction to Europe's recurrent cholera epidemics since 1831. While historians have long stressed the dominance of aesthetical and industrial over sanitary concerns, the study of Berlin's contemporary discourse suggest that the causal link between cholera and water infrastructure reform was not only weak, but ambiguous. Far from motivating the right actions for the wrong reasons, cholera's conception through the dominant miasmatist frameworks and limited proto-epidemiological tools of the prebacteriological era inspired inefficient, at times even counterproductive approaches that potentially deepened the urban mortality penalty. Berlin's role as a political and scientific center of 19th century Europe suggests that her experience was the norm rather than the exception. A nuanced understanding of Western Europe's sanitary past has important implications for the continuing struggle for urban sanitation in today's developing world.
Keywords: N33; N53; N93; 330; Cholera; Water-Borne Disease; Epidemic; Sanitation; Berlin; Germany; Tap Water; Sewers; 19th Century; Miasma; Mortality; Urban Penalty